The importance of a proof reader in translation / Amirah Izzati Syahrul Ahmar and Jean Hoo Fang Jing - Syahrul Ahmar, Amirah Izzati; Fang Jing, Jean Hoo (Akademi Pengajian Bahasa, 2021)
A translated document must be ensured of the originality and convey the same meaning. Though much of translations are being automated now, proofreading is one area where human intervention is required to deliver high quality translations. Professional human proofreaders can do so to the best of their knowledge, capacities, and abilities. Often, it is regarded as insignificant unless necessary in the industry. However, this paper aims to emphasize the needs to proofreading in translated documents to further strengthen its functionality. The objective of this paper is to prove that unproofread translations will contain errors. The effects of poorly translated materials will impact the translators’ performance and their customers’ feedback. Although technology has been proven effective in the translation and proofreading area, there are doubts on its preciseness. Therefore, proofreading should be included in the final step of translation. To obtain the goal, a qualitative research has been conducted to highlight on a machine’s inability to offer accurate results. The findings proved that proofreading should be implemented in translation. Hence, a discourse analysis was performed on three websites; SOCSO, Zakat, and Tabung Haji to support the statement. The resultant distinguished a few errors in the websites from word misusage, mistranslations, punctuation, capitalization, formatting, spelling, and sentence structure. As expected, the oversights occurred both in the source and target text. In brief, the presence of a proofreader is highly encouraged and should be considered mandatory to maintain the quality and efficiency of a translator’s service.